2019
DOI: 10.3390/ma12233958
|View full text |Cite
|
Sign up to set email alerts
|

Glassy Magnetic Behavior and Correlation Length in Nanogranular Fe-Oxide and Au/Fe-Oxide Samples

Abstract: In nanoscale magnetic systems, the possible coexistence of structural disorder and competing magnetic interactions may determine the appearance of a glassy magnetic behavior, implying the onset of a low-temperature disordered collective state of frozen magnetic moments. This phenomenology is the object of an intense research activity, stimulated by a fundamental scientific interest and by the need to clarify how disordered magnetism effects may affect the performance of magnetic devices (e.g., sensors and data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…This indicates that higher anisotropy energy barriers are associated with the C26 MNPs, compared to C5 and C12, certainly due to their larger mean size and wide size distribution, good crystallinity, and stronger dipolar interactions also by virtue of the higher M S . In this last respect, the abrupt decrease of M ZFC below ~40 K is reminiscent of a long-range collective freezing of the MNPs magnetic moments under the action of dipolar interactions, probably involving the smaller MNPs of the assembly [82][83][84]. Above T ~40 K, the linear rising trend of M ZFC , typical of a ferromagnet, confirms the presence of non-relaxing MNPs, which coexist with the fraction of relaxing ones.…”
Section: Magnetic Propertiesmentioning
confidence: 82%
“…This indicates that higher anisotropy energy barriers are associated with the C26 MNPs, compared to C5 and C12, certainly due to their larger mean size and wide size distribution, good crystallinity, and stronger dipolar interactions also by virtue of the higher M S . In this last respect, the abrupt decrease of M ZFC below ~40 K is reminiscent of a long-range collective freezing of the MNPs magnetic moments under the action of dipolar interactions, probably involving the smaller MNPs of the assembly [82][83][84]. Above T ~40 K, the linear rising trend of M ZFC , typical of a ferromagnet, confirms the presence of non-relaxing MNPs, which coexist with the fraction of relaxing ones.…”
Section: Magnetic Propertiesmentioning
confidence: 82%
“…This technique also has been proposed to probe the spin disorder in magnetic nanoparticles [126]. For example, Toro et al reported that the dips in the DeltaM plots, calculated by subtracting the remanence curves, are not necessarily due to the interaction fields as they could be due to spin disorder, an inhomogeneity of spin distributions in the magnetic nanoparticles [127].…”
Section: Remanence Curves Techniquementioning
confidence: 99%